2017
DOI: 10.18844/prosoc.v3i5.2002
|View full text |Cite
|
Sign up to set email alerts
|

A child with Down syndrome - Challenge for families, kindergartens and schools

Abstract: Every day, the number of children born with disabilities is increasing. One of the many disabilities is Down's syndrome, which occurs on average in one of 650 infants. For a child born with this disability, it is much more difficult to normally grow, develop and function in everyday life. In the past, children born with Down syndrome were neglected, and their education was not paid almost any attention. Today, there are significant changes in social awareness related to rights and needs of children with Down s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Timely announcements can direct students to the acceptance of students with disabilities, but the actual value is achieved through those who live and work together." (Duranovic, M., Klasnic, I., & Opic, V., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Timely announcements can direct students to the acceptance of students with disabilities, but the actual value is achieved through those who live and work together." (Duranovic, M., Klasnic, I., & Opic, V., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Mainstream schooling has better outcomes for children who have Down syndrome. Research has shown that students with Down syndrome gain academic, social and behavioral advantages from being educated with their typically developing peers in mainstream schools (Buckley et al, 2006;Down Syndrome Ireland, 2018).…”
Section: Acceptance Towards Individuals With Down Syndromementioning
confidence: 99%
“…People with DS manifests over fifty distinctive features that varies child to child, however most of the people does have very fundamental knowledge about it, even in an advanced and developed country like the US.Children with DS are amiable, pleasant, and social; however, they do go with the same level of emotional development, therefore, selective conditioning is required with them. Duranovic et al mentions that children with DS are less creative, therefore, the role of an educator plays an integrative role by indulging them into interactive games and exercise 19 .…”
Section: Introductionmentioning
confidence: 99%